A J-domain protein enhances memory by promoting physiological amyloid formation in Drosophila - Kyle Patton; Yangyang Yi; Raj Burt; Kevin Kan-Shing Ng; Mayur Mukhi; Peerzada Shariq Shaheen Khaki; Ruben Hervas; Kausik Si (Proceedings of the National Academy of Sciences, 2026)
Memory requires experience-dependent alterations in the synaptic proteome. Chaperones interface between the environment and the proteome. Manipulating J-domain protein (JDP) chaperones, the most diverse family of chaperones, in a Drosophila neuronal circuit that encodes associative long-term memories, we identified yet uncharacterized JDPs that transduce sensory cues. One of these JDPs, CG10375, which we named Funes, enhances memory when overexpressed and impairs memory when functionally impaired. Funes overexpression enhances memory formation even when sensory stimuli are suboptimal. At the circuit level, Funes acts on neurons where conditioned and unconditioned stimuli converge to form associative memories. From a proteomic-based screen, we found that overexpression of Funes changes the solubility of a small subset of proteins, one of which is the mRNA-binding protein Orb2. Combining in vitro and in vivo biophysical, biochemical, and cryo-EM structural analyses, we found that Funes associates with oligomeric Orb2 and promotes the formation of translationally active amyloids. Perturbation of the conserved J domain eliminates the ability of Funes to facilitate amyloid assembly and promote memory. We posit that the brain harbors chaperones that influence memory by regulating physiological amyloid formation.